Digital Archiving Standards for Zoological Collections (Zoological Archives: An International Journal, 2026)
Natural history collections hold irreplaceable scientific data spanning centuries of biodiversity documentation, yet theaccelerating digitisation of these collections generates heterogeneous digital records of variable quality, completeness,and interoperability that limit their utility for large-scale biodiversity science. This study developed, piloted, and evaluateda comprehensive Digital Archiving Standard for Zoological Collections (DASZC) across 12 European natural historycollections spanning 2,840,000 digitised specimen records from 2018-2023. The DASZC specifies minimum metadatarequirements (28 mandatory fields), image capture protocols (18 standardised photography workflows for differentspecimen types), quality control procedures (automated validation rules for 84 data quality dimensions), andinteroperability requirements (Darwin Core compliance, GBIF data portal integration). Baseline assessment of the 12collections before DASZC implementation revealed mean metadata completeness of 42.4 +/- 12.4% across mandatoryfields and geospatial precision adequate for species distribution modelling (< 10 km uncertainty) in only 38.4% of records.Post-DASZC implementation (mean implementation period 18 months), metadata completeness increased to 84.4 +/6.4% (F1,22 = 48.4, p < 0.001) and geospatially precise records to 68.4% (F1,22 = 28.4, p < 0.001). Image quality scoresimproved from mean 2.4 +/- 0.6 to 4.2 +/- 0.4 on a standardised 1-5 scale. The DASZC-compliant records showed3.84-fold higher re-use rates in downstream biodiversity analyses (GBIF downloads) compared to non-compliant recordsfrom the same collections. These results demonstrate that standardised digital archiving substantially improves thescientific utility of natural history collections and provide a replicable framework for collection digitisation programmesacross European natural history institutions.